Paclitaxel-carboplatin chemotherapy induced hematologic toxicities among epithelial ovarian cancer patients - Charles, Afandi; Dewayani, Birgitta M.; Sahiratmadja, Edhyana; Winarno, Gatot N.A.; Susanto, Herman (Faculty of Medicine, Trisakti University, 2016)
BackgroundEpithelial ovarian cancer (EOC) is one of the most common cancers diagnosed in Indonesian women. A combination of paclitaxel and carboplatin is used to treat EOC as standard chemotherapy which is known to have hematologic toxicities. This study aimed to investigate the effect of combined paclitaxel-carboplatin chemotherapy on hematologic status in EOC patients managed at Dr. Hasan Sadikin General Hospital, Bandung, West Java.MethodsAll patients with confirmed pathological diagnosis of EOC at Dr. Hasan Sadikin General Hospital in the period of 2013 to 2014 were registered. Only patients with complete hematologic data before and after chemotherapy were collected and compared using the paired non-parametric Wilcoxon and McNemar tests. ResultsIn total there were 147 patients with EOC (median age 46 Â± 12 years), with the most dominant pathological diagnosis of mucinous (32.7%) and serous (29.3%) types. Only 33 patients had hematologic data before the initiation of chemotherapy. There was a significant decrease after chemotherapy including hemoglobin level (12.0 vs 10.9 g/dL, p=0.013), erythrocyte count (4.53 vs 3.74 million/mL, p<0.001), leukocyte count (7,700 vs 4,000/mm3 p<0.001) and platelet count (343,000 vs 215,000/mm3, p<0.001). Interestingly, anemia cases after chemotherapy were predominant (87.9%) compared with erythopenia, leukopenia, thrombocytopenia i.e. 39.4%, 57.6%, and 27.3% respectively. ConclusionsThis study confirmed the hematologic toxicities after paclitaxel-carboplatin chemotherapy in EOC patients treated in Hasan Sadikin General Hospital, West Java. The hemoglobin concentration may serve as prognostic factor. Further studies directed to other factors such as genetic factor for polymorphisms may be encouraged to explore the decrease of the hematologic indices.